The Influence of Teachers' Readiness Level and Motivation on The Implementation of The Merdeka Curriculum (IKM) in North Ternate City - Ramdani Salam; Putri Adibatur Rohmah; Syarifuddin Adjam; Asnita Ode Samili; Muhlis Malaka (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This research explores the implementation of The Merdeka Curriculum (IKM) in North Ternate City, focusing on the influence of teachers' readiness level and motivation. The research used quantitative, using surveys to gather data from 68 junior high school teachers in North Ternate City who implemented The Merdeka Curriculum (IKM). The research indicates that the readiness level of teachers influences 0.65, while teacher motivation has an influence of 0.72 on the success of implementing the Merdeka Curriculum (IKM) in Ternate City. With significant coefficients, it can be concluded that both teacher readiness and motivation have a positive and significant impact on the quality of teaching IKM and student success in Ternate City. Enhancing teacher readiness and motivation can be an effective strategy to improve the quality of education through the effective implementation of IKM.